100+ GHz static divide-by-2 circuit in InP-DHBT technology. - Mokhtari, M.
Static dividers in 135-GHz InP-DHBT technology have been designed, fabricated, and measured. Circuits are operational from dc to 100 GHz. Due to limitations in available measurement equipment, adequate investigation of the circuit operation beyond 100 GHz is not possible at this time, however, to the authors' knowledge, this is already the highest toggling frequency reported in any static circuit in any technology. The circuit has a total area of 675×900 μm2, with the core of the flip-flop occupying about 240×170 μm2.
Keywords: 0 to 100 GHz; InP; InP DHBT technology; Flip-flop.; High-speed IC; Static divide-by-two circuit; Toggling frequency